Efektivitas E-Government Melalui Web Room to Read dalam Meningkatkan Minat Baca Khususnya Peserta Didik - Ima Nur Rosyida; Kendry Widiyanto (Politeknik Kampar, 2023)
In recent years the progress of information technology and communication has seen unprecedented growth. Furthermore, governments are currently being confronted communities that demand service effective and efficient electronic based. E-Government refers to government service to communities, businesses and other organizations that utilize information technology and communication. Thus, all sectors ranging from the government sector to the private sector practice a lot of electronic based service. In this study, researchers applying a descriptive approach to a qualitative research approach. The result of this study indicate that effectiveness of e-government through web room to read has been successful in help communities particularly learners in increase read interest. Web room to read program own a vital role in improving reading interest in both home and school environment. And ascertain that communities and students become major contributors in raising the number of reading interests Indonesian communities.